(untitled) (Kohesi: Jurnal Sains dan Teknologi, 2025)
The development of information system technology, especially in the field of mobile devices, has had a significant impact on the business world, including in the car rental sector. Aqila Rental Business faces challenges in managing data and transaction processes that are still carried out manually, which causes inefficiencies in service, such as a long rental process and the inability of customers to access vehicle information in real time. This study aims to design and build an Android-based car rental application to facilitate the process of ordering and managing rental data. This application is built using Android Studio using the Java programming language, MySQL and PHP-based data storage, and allows online access to provide convenience for users and managers. The results of this study indicate that by building an Android-based car rental application, an efficient and organized system can be built, which improves the user experience in making reservations, speeds up the transaction process, and provides better service. This application also makes it easier for business managers to manage vehicle data, customer data, and transactions in real time, thereby increasing the operational efficiency of the car rental business